Determining the effects of branched chain amino acids, manganese, and xylanase on growing-finishing pig growth performance and carcass characteristics - Kerkaert, Hayden Richard (Kansas State University, 2020)
Experiment 1 used a total of 1,200 pigs to determine the effects of added Val, Ile, and Trp in high Leu on growing-finishing pig growth performance and carcass characteristics in order to validate a prediction model. Experiments 2 and 3 used a total of 3,888 pigs to determine the effects of manganese source and level on growing-finishing pigs growth performance and carcass characteristics. Experiment 4 used a total of 1,944 pigs to determine the effects of increasing added xylanase in nutrient adequate diets on growing-finishing pigs growth performance and carcass characteristics. Experiment 1 determined that increasing Val or Ile in high Lys-HCl-DDGS-based diets improved growth performance and final BW compared with pigs fed diets containing high levels of Lys-HCl without added Val and Ile. The addition of Trp alone could not overcome the negative effects of growth performance of pigs fed high Leu diets. These results demonstrate that negative effects of high Leu concentrations in corn-DDGS-based diets can be reversed by increasing the ratios of Val and Ile to Lys. In Exp. 2 and 3, growth performance was improved when 8 and 32 mg/kg of Mn is supplemented compared to 16 mg/kg and when pharmacological levels of Cu are supplemented; pigs fed Mn hydroxychloride had improved growth performance. Also, as Mn concentration in the diet increased, regardless of source, total Mn concentration in the liver increased but increased less for pigs fed Mn hydroxychloride. In Exp. 4, when xylanase was added to nutrient adequate diets, there was improved carcass yield when intermediate levels were fed, however, there was no impact on growth performance or mortality.
Keywords: Branched chain amino acids; Manganese; Pig; Xylanase